2021
DOI: 10.3390/ijms22094985
|View full text |Cite
|
Sign up to set email alerts
|

Effectors of Puccinia striiformis f. sp. tritici Suppressing the Pathogenic-Associated Molecular Pattern-Triggered Immune Response Were Screened by Transient Expression of Wheat Protoplasts

Abstract: Puccinia striiformis f. sp. tritici (Pst) is an important pathogen of wheat (Triticum aestivum L.) stripe rust, and the effector protein secreted by haustoria is a very important component involved in the pathogenic process. Although the candidate effector proteins secreted by Pst haustoria have been predicted to be abundant, few have been functionally validated. Our study confirmed that chitin and flg22 could be used as elicitors of the pathogenic-associated molecular pattern-triggered immune (PTI) reaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…By contrast, B. distachyon produced ROS after the recognition of flg22. Leaf disks of monocotyledonous plants, including wheat, barley, sorghum, and maize, were reported to produce ROS in response to flg22 ( Proels et al., 2010 ; Zhang et al., 2017 ; Samira et al., 2020 ; Su et al., 2021 ), suggesting that these plant species recognize flg22 as a MAMP. The relative light unit (RLU) value in response to chitinheptaose was similar to that in response to flg22 ( Figure 1 ), indicating that B. distachyon fully responds to flg22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, B. distachyon produced ROS after the recognition of flg22. Leaf disks of monocotyledonous plants, including wheat, barley, sorghum, and maize, were reported to produce ROS in response to flg22 ( Proels et al., 2010 ; Zhang et al., 2017 ; Samira et al., 2020 ; Su et al., 2021 ), suggesting that these plant species recognize flg22 as a MAMP. The relative light unit (RLU) value in response to chitinheptaose was similar to that in response to flg22 ( Figure 1 ), indicating that B. distachyon fully responds to flg22.…”
Section: Discussionmentioning
confidence: 99%
“…In tomatoes, flgII-28 is recognized by FLS3 RLK in a BAK1-dependent manner ( Hind et al., 2016 ). In monocotyledonous plants such as wheat ( Triticum aestivum ), barley ( Hordeum vulgare ), sorghum ( Sorghum bicolor ), and maize ( Zea mays ), leaf disks have been shown to produce ROS in response to flg22 ( Proels et al., 2010 ; Zhang et al., 2017 ; Samira et al., 2020 ; Su et al., 2021 ). Interestingly, rice plants and cultured cells showed a weak response to flg22, although they could recognize flagellin extracted from Acidovorax avenae .…”
Section: Introductionmentioning
confidence: 99%
“…This has also been successfully used in the identification of rust effectors acting at many sites in the plant cell compartments. In a recent study, the transient expression system of mesophyll protoplasts was found to be an important and useful tool for studying signal transduction in pathogen-model plant interactions ( Su et al, 2021 ). Chitin and flg22 can be used as triggers for the PTI response in wheat leaves and TaPr-1-14 can also be used as a marker gene for detecting the PTI response.…”
Section: Methods Of Researching Effectors Of Biotrophic Plant Fungal ...mentioning
confidence: 99%
“…Chitin and flg22 can be used as triggers for the PTI response in wheat leaves and TaPr-1-14 can also be used as a marker gene for detecting the PTI response. Screening and identification of Pst effector proteins can be performed rapidly and efficiently using a transient wheat protoplast expression system ( Su et al, 2021 ). Out of 39 haustorial effector genes that were successfully screened and cloned using the protoplast transient expression system, three haustorial effector proteins PSEC2, PSEC17, and PSEC45 were identified and had the ability to inhibit wheat response to PTI.…”
Section: Methods Of Researching Effectors Of Biotrophic Plant Fungal ...mentioning
confidence: 99%
See 1 more Smart Citation